2020
DOI: 10.1016/j.annonc.2020.10.375
|View full text |Cite
|
Sign up to set email alerts
|

381MO Durability of clinical benefit and biomarkers in patients (pts) with advanced non-small cell lung cancer (NSCLC) treated with AMG 510 (sotorasib)

Abstract: Conclusions: Across all arms, pts with PFS 12m had exceptional 2 yr OS rates >75%, despite some having poor prognostic factors such as baseline brain or liver metastases. There were >3 times more pts deriving long-term benefit when treated with durvalumab + EP vs EP alone. Further investigation into predictive factors for longterm benefit with durvalumab is ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Such drugs will likely have lower toxicity than those targeting both wild-type and mutant protein. Many pharmaceutical companies are now developing more potent inhibitors of KRAS G12C ; some of these are entering clinical trials, while others remain in early development (Table 1) [11][12][13][14][15][77][78][79][80][81][82].…”
Section: Direct Inhibition Of Krasmentioning
confidence: 99%
See 1 more Smart Citation
“…Such drugs will likely have lower toxicity than those targeting both wild-type and mutant protein. Many pharmaceutical companies are now developing more potent inhibitors of KRAS G12C ; some of these are entering clinical trials, while others remain in early development (Table 1) [11][12][13][14][15][77][78][79][80][81][82].…”
Section: Direct Inhibition Of Krasmentioning
confidence: 99%
“…However, subgroup sample sizes were small and future prospective studies are warranted. Clinical activity was also demonstrated across a range of mutational allele frequencies, PD-L1 expression levels, and tumor mutational burden (TMB) levels [13,77]. Finally, an analysis of patient-reported outcome measures from CodeBreaK 100 suggested that sotorasib maintained or improved quality of life, physical functioning, and the severity of key lung cancer-related symptoms [88].…”
Section: Sotorasibmentioning
confidence: 99%
“…An interesting report has shown that NSCLC patients treated with sotorasib, a KRAS G12C inhibitor, achieved disease control leading to a median progress free survival (PFS) of 6.9 months. However, this current limited dataset suggests that neither KRAS p.G12C MAF nor PD-L1 expression level predicts response to sotorasib [ 46 ]. Meanwhile, tumor therapy targeting m 6 A modification has attracted researchers’ attention.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that cases with STK11 and TP53 co-occurring mutations responded better to sotorasib than patients harboring KEAP1 co-mutation [ 169 , 170 , 171 , 173 , 174 , 175 ]. Moreover, alterations in cell cycle effectors like in the WNT and MAPK pathways are more common in the late progressors group [ 176 ].…”
Section: Current Therapeutic Approaches and Perspectives In ...mentioning
confidence: 99%